Radio frequency interference mitigation using deep convolutional neural networks - Akeret, J.; Chang, C.; Lucchi, A.; Refregier, A. (Astronomy and computing, 2017)
We propose a novel approach for mitigating radio frequency interference (RFI) signals in radio data using the latest advances in deep learning. We employ a special type of Convolutional Neural Network, the U-Net, that enables the classification of clean signal and RFI signatures in 2D time-ordered data acquired from a radio telescope. We train and assess the performance of this network using the HIDE &SEEK radio data simulation and processing packages, as well as early Science Verification data acquired with the 7m single-dish telescope at the Bleien Observatory. We find that our U-Net implementation is showing competitive accuracy to classical RFI mitigation algorithms such as SEEK’s SumThreshold implementation. We publish our U-Net software package on GitHub under GPLv3 license.